یہود کےفکری مغالطوں کا قرآنی بیانیہ: Quranic Narrative on Fallacies of Jews - Muhammad Riaz; Dr. Muhammad Atif Aslam Rao (MEI, 2023)
Among various nations, Jews have always been a conspiring and cunning nation. They have a long-standing claim that they are the only God's chosen people. This nation has always repulsed the truth. Allah Almighty sent many prophets to reform their beliefs and deeds. However, they remained steadfast in their nature and remained in disbelief and disobedience. This article deals with fallacies of Jews and deeply examines the misconceptions and misunderstandings of the Jews in the light of selected verses of the Qur’an. The researchers have introduced their subject with a brief history of Jews. Subsequently, comprehensive discussion is made on various fallacies of Jews along with the Quranic Narrative on them. Among numerous false notions, research is presented on their beliefs on being the only pious and son of Almighty Allah who truly deserve Heaven. It also deals with their belief that all prophets were Jews and it is sufficient to believe only on Taurah. The article also presents the cause of their misbehavior that Jews deliberately commit sin and assume that they will be forgiven by Allah. As a result of this misunderstanding, they neither repent nor feel ashamed. Jews have always rebelled the truth. They killed the Prophets unjustly, turned away from the truth, distorted the Book of Allah and broke the covenant. This attitude is continued till present. It is highly significant to highlight their fallacies to the modern-day researchers and students in the context of the Holy Quran so that the nation can secure themselves and their upcoming generations.